TerrorBot- Python Based Cascade Classifier to Detect Terrorists and Soldiers - R, Kavya; A, Keerthana; HN, Keerthana; KN, Meena; Srinivas, Chetana (International Journal of Computer Sciences and Engineering, 2025)
Most of the defense organization now takes the help of robots to carry out many risky jobs that cannot be done by soldiers. These robots used in defense or usually employed with integrated system, including video screens, sensors, laser gun, metal detector and cameras. The defense robots also have different shapes according to various purposes. Here the new system is proposed with the help of camera through we can trace out the intruders and the robot will be employed with integrated system, including video camera, sensors, gripper and weapon. The intruders face detection by Haar Cascade Classifier and face recognition by LBPH (Local Binary Pattern Histogram). This is specially designed robotic system to protect the country from enemies and to save soldiers life. The proposed algorithm is implemented using Opensource Computer Vision (OpenCV) and image processing with python.